Legislation - Ali Mohamed, Ashgar Ali (CLJ Publication, 2020)
The doctrine of separation of powers propounded by English philosopher, John Locke, and the French writer, Baron de Montesquieu, described the separation of political power among the legislature, executive, and judiciary. It states, inter alia, that the legislative, executive and judicial functions of Government should be discharged by independent institutions that springs from a desire to prevent the over-concentration of power in the hands of a few and to ensure that the Government is responsible and accountable. The power to legislate law is with the legislature, the application of the enacted legislation is on the executive and its subjects and the power to interpret the legislation and of ensuring its compliance lies with the courts